A influência da atividade física escolar na prevalência da obesidade infantil como um indicador para a promoção de saúde e sua relação com aspectos familiares e sócio-econômicos - Costa, Célia Regina Bernardes (2008)
This study aimed at evaluating the influence of physical activity on the school environment and its possible relationship with obesity prevalence in public and private elementary school students in the city of Patos de Minas – MG. Three hundred students aged 8 to 11 years, of socioeconomic status A and B, and also C, D and E, distributed in three schools, a private school, a state school and a municipal school were analyzed. The students’ body mass index (BMI) was calculated and students were classified in underweight, normal weight and overweight. Possible correlations among the variables physical activity, familial history and socioeconomic status were also performed. The public school students of socioeconomic status C, D and E not only showed elevated values of obesity but also greater proportion of underweight. The results also point to genetics effects on obesity since the number of obese in the family of overweight children aged 8 to 9 years of socioeconomic status C, D and E was also significant. In the weekly amount of in-school physical activity, children who attend at least three classes showed obesity prevalence of 0%. By and large, all these factors have a direct relationship with childhood obesity. Also, the practice of physical activities could improve students’ quality of life within the cohort studied, aiding in childhood obesity control and children’s health. Hence, it can be suggested that in-school physical activity, isolated or associated, plays an important role in the prevention and control of childhood obesity mainly when it comes to children of low socioeconomic status. It is recommended that this discussion be fostered in debates concerning federal, state and municipal health promotion public policies, taking into account its low cost and its high efficiency. Keywords: Students; Physical Education; Physical Activity; Obesity; Health Promotion.